Cardiac electrophysiology from cell to bedside - Zipes, Douglas P.; Jalife, José; Stevenson, William G. (Elsevier, 2018)
"Rapid advancements in cardiac electrophysiology require today's health care scientists and practitioners to stay up to date with new information both at the bench and at the bedside. The fully revised 7th Edition of Cardiac Electrophysiology: From Cell to Bedside, by Drs. Douglas Zipes, Jose Jalife, and William Stevenson, provides the comprehensive, multidisciplinary coverage you need, including the underlying basic science and the latest clinical advances in the field"--Publisher's description